Public Attitudes toward Consent When Research Is Integrated into Care—Any "Ought" from All the "Is"?. Issue 2 (11th April 2021) - Morain, Stephanie R.; Largent, Emily A.
Abstract: Research that is integrated into ongoing clinical activities holds the potential to accelerate the generation of knowledge to improve the health of individuals and populations. Yet integrating research into clinical care presents difficult ethical and regulatory challenges, including how or whether to obtain informed consent. Multiple empirical studies have explored patients' and the public's attitudes toward approaches to consent for pragmatic research. Questions remain, however, about how to use the resulting empirical data in resolving normative and policy debates and what kind of data warrants the most consideration. We recommend prioritizing data about what people consider acceptable with respect to consent for pragmatic research and data about people's informed, rather than initial, preferences on this subject. In addition, we advise caution regarding the weight given to majority viewpoints and identify circumstances when empirical data can be overridden. We argue that empirical data bolster normative arguments that alterations of consent should be the default in pragmatic research; waivers are appropriate only when the pragmatic research would otherwise be impracticable and has sufficiently high social value .